Given:
[tex]4\sqrt{7}-2(2\sqrt{7}+\sqrt{3})+\sqrt{12}[/tex]
To find:
The value of given expression.
Solution:
We have,
[tex]4\sqrt{7}-2(2\sqrt{7}+\sqrt{3})+\sqrt{12}[/tex]
It can be written as
[tex]=4\sqrt{7}-2(2\sqrt{7}+\sqrt{3})+\sqrt{4\times 3}[/tex]
[tex]=4\sqrt{7}-2(2\sqrt{7}+\sqrt{3})+2\sqrt{3}[/tex]
Using distributive property, we get
[tex]=4\sqrt{7}-2(2\sqrt{7})-2(\sqrt{3})+2\sqrt{3}[/tex]
[tex]=4\sqrt{7}-4\sqrt{7}-2\sqrt{3}+2\sqrt{3}[/tex]
[tex]=0[/tex]
Therefore, the value of given expression is 0.